2016
DOI: 10.1128/jcm.01082-16
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: The Future of Whole-Genome Sequencing for Public Health and the Clinic

Abstract: health pathogen surveillance were presented at the meeting and are reviewed. All of these studies document that WGS is revolutionizing applications in microbiology and that the impact of these technologies will be profound. ASM is providing support mechanisms to promote discussions of WGS techniques to foster applications and interpretations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 7 publications
0
23
0
1
Order By: Relevance
“…The evolution of sequencing technologies [1, 2] encouraged many applications of Whole Genome Sequencing (WGS) and Whole Exome Sequencing (WES) in genomic research and the clinic [3, 4]. One of these applications is genomic variant calling, commonly performed using the Genome Analysis Toolkit (GATK), maintained by the Broad Institute [5–8].…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of sequencing technologies [1, 2] encouraged many applications of Whole Genome Sequencing (WGS) and Whole Exome Sequencing (WES) in genomic research and the clinic [3, 4]. One of these applications is genomic variant calling, commonly performed using the Genome Analysis Toolkit (GATK), maintained by the Broad Institute [5–8].…”
Section: Introductionmentioning
confidence: 99%
“…Whole-genome sequence (WGS) data is increasingly important in public health microbiology (14). The data can be used to replicate many of the basic bacterial sub-typing approaches, as well as support epidemiological investigations, such as surveillance and outbreak investigation (57).…”
Section: Announcementmentioning
confidence: 99%
“…Currently routine WGS in clinical microbiology is most suited to public health and reference laboratories and is unlikely to be adopted on a widespread basis by individual hospitals in the short-term and many factors need to be considered, including cost, infrastructure, sequencing capacity and data analysis capabilities [ 78 ]. Further cost reductions, technological developments and perhaps most importantly, overcoming challenges associated with bioinformatic analysis [ 78 , 79 , 80 ] will all aid the more widespread adoption of WGS in clinical settings. Finally, a recent study has shown that significant monetary savings (in excess of €200,000 in this case) can be achieved by adopting WGS to inform more targeted infection control policies [ 81 ].…”
Section: Whole-genome Sequencingmentioning
confidence: 99%